Dental management of Rapp-Hodgkin syndrome associated with oral cleft and hypodontia - Shanmugasundaram Karthikeyani; Velliangattur Ramasamy Thirumurthy; Bindhoo A Yuvaraja (Wolters Kluwer Medknow Publications, 2016)
Rapp-Hodgkin syndrome (RHS) is a rare type of autosomal dominant disorder characterized by association of ectodermal dysplasia (ED) with cleft lip/palate. The main features include dry, brittle hair with alopecia in adulthood, dental anomalies (hypodontia, microdontia with delayed eruption, fissured tongue, and retruded maxilla), hypohidrosis, dysplastic nails, and clefting. Palmar-plantar keratoderma is seen frequently. RHS has signs and symptoms that overlap considerably with those of ankyloblepharon-ED-clefting syndrome and ectrodactyly-ED-clefting syndrome. This manuscript discusses a case of RHS, one of the four members in three generations who had ED with variable degree of involvement of hair, teeth, nail, and sweat glands.